Surface Resistivity Sounding and Borehole Data Analysis for the Evaluation of Aquifer Characteristics of Southern Districts Barguna and Patuakhali, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
The study delineates the aquifer system of the study area and determines the extension of potential fresh water aquifer and suitable locations for groundwater development through geophysical electrical resistivity method. Vertical electrical sounding with Schlumberger electrode configuration, a method for surface resistivity measurement, has been used for data collection. Resistivity data along with borelog data analyses are used for this investigation. Lithological cross section analyses show that sand and clay dominated lithology with frequent facies changes occur throughout the area and also show an aquifer system similar to the three-tier aquifer system proposed by Aggarwal for coastal area of Bangladesh. This study reveals the presence of three aquifers. 1staquifer occurs at a very shallow depth at some places